MODIFIKASI PERMAINAN ULAR TANGGA SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA BAGI SISWA KELAS 2 SD NEGERI 2 PENGKOL KEC. KARANGGEDE - Nasywa T Rasyid; Muhammad Setiyawan (PT. Hasba Edukasi Mandiri, 2026)
Board games are educational tools that support collaboration among students, help achieve learning objectives, broaden children's knowledge, and serve as a source of motivation in the learning process. At SD Negeri 2 Pengkol, Karanggede District, mathematics is often considered a difficult subject because the teaching methods used do not fully match students' learning styles, particularly in understanding abstract concepts. This study aims to develop and implement a modified snakes-and-ladders game as a mathematics learning medium, focusing on addition, subtraction, multiplication, and division for second-grade students at SD Negeri 2 Pengkol. The research combines qualitative and quantitative approaches through field observation and interviews with teachers and students. The results show that the modified snakes-and-ladders game effectively improves students' understanding of the material, increases their enthusiasm and engagement in learning, and receives a positive response from teachers as a learning aid.